PENGEMBANGAN E-MODUL FLIPBOOK BERBASIS PENDIDIKAN KARAKTER TRI NGA (NGERTI, NGRASA, NGELAKONI) PADA MATERI GOTONG ROYONG MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SEKOLAH DASAR - Robby Nurcahyo; Urip Tisngati; Khoirul Qudsiyah (PGSD STKIP PGRI Pacitan, 2026)
This study was conducted to develop a flipbook-based e-module integrating the Tri Nga character education values (Ngerti, Ngrasa, and Nglakoni) into the topic of Mutual Cooperation (Gotong Royong) in the Pancasila Education subject for fifth-grade elementary school students, as well as to evaluate the feasibility of the product. The study employed a Research and Development (R&D) approach using the 4D model, which was modified by limiting the process to the Develop stage, consisting of Define, Design, and Develop. Data were collected through observation sheets, interview guidelines, validation sheets completed by subject matter experts and media experts, and student response questionnaires. The data were analyzed using descriptive quantitative techniques. The results indicated that the flipbook-based e-module was classified as highly feasible, with a feasibility score of 95% from the subject matter experts and 94% from the media experts. In addition, student responses reached 95%, which fell into the very good category. These findings indicate that the developed flipbook-based e-module is suitable for use as a learning medium in Pancasila Education, particularly for teaching the topic of Mutual Cooperation (Gotong Royong) to fifth-grade elementary school students.